Epidemiology of road traffic accidents in cats attending emergency‐care practices in the UK. (1st November 2018) - Conroy, M.; O'Neill, D.; Boag, A.; Church, D.; Brodbelt, D.
Abstract : Objectives: To estimate the incidence proportion of road traffic accidents in cats attending emergency out‐of‐hours clinics in the UK, identify major risk factors for road traffic accident occurrence and for survival to discharge. Materials and Methods: A retrospective study of a cohort of 33, 053 cats in the VetCompass database attending emergency‐care practice between January 1, 2012 and February 15, 2014. Incidence proportion was calculated and logistic regression was used to identify risk factors for road traffic accident and survival to discharge following road traffic accident. Results: Incidence proportion was estimated at 4∙2% (95% confidence interval: 4∙0 to 4∙4%). Cats aged 6 months to 2 years were at increased odds of road traffic accident, as were male cats and crossbred cats. Odds of road traffic accident were highest in the autumn. Spinal injury, abdominal injury and increasing count of injuries were associated with increased odds of death. Clinical Significance: Road traffic accident is a frequent presentation in emergency‐care practice. Identification of risk factors for death within the first 24 hours following a road traffic accident can aid veterinarian and owner decision‐making for treatment of cats involved in a road traffic accident.